Qual o impacto da pesca de arrasto sobre a assembleia de camarões em áreas costeiras marinhas? Uma análise temporal de populações a ecossistema no litoral norte de São Paulo - Perroca, Júlia Fernandes [UNESP] (2023)
Different life cycles lead to differences in species niche and in their ecological requirements. In this study we registered the spatial and temporal variance in abundance in eight shrimp species by analyzing a dataset that spanned a 27-year period. We also assessed the influence of ocean-climatic and environmental factors in their abundance. Periods of neutrality favored the increase in abundance of Artemesia longinaris, Pleoticus muelleri, Rimapenaeus constrictus, Sicyonia dorsalis and Nematopalaemon schmitti. The shrimps P. muelleri and S. dorsalis also showed higher abundances in periods of La Niña. In La Niña and neutral periods, there is a shift in the atmospheric pressure gradient favoring Northeast winds, that enhances the SACW intrusion and weakens the Coastal Water. Thus, species that responds negatively to elevated temperatures, as P. muelleri and S. dorsalis, in El Niño will migrate to deeper areas, which were not sampled in this study. As for El Niño events, it favored the abundance of Litopenaeus schmitti and R. constrictus. El Niño is known to increase water surface temperature in southeast Brazil, so the increase in temperature is benefic to these species whose abundances increase in elevated temperatures. All species were associated with sediments of silt and clay. Long-term monitoring of the communities of species of commercial interest or accidentally captured, are essential for establishing standards and measures to protect ecosystems.